2016
DOI: 10.1371/journal.pone.0151803
|View full text |Cite
|
Sign up to set email alerts
|

A Role of hIPI3 in DNA Replication Licensing in Human Cells

Abstract: The yeast Ipi3p is required for DNA replication and cell viability in Sacharomyces cerevisiae. It is an essential component of the Rix1 complex (Rix1p/Ipi2p-Ipi1p-Ipi3p) that is required for the processing of 35S pre-rRNA in pre-60S ribosomal particles and for the initiation of DNA replication. The human IPI3 homolog is WDR18 (WD repeat domain 18), which shares significant homology with yIpi3p. Here we report that knockdown of hIPI3 resulted in substantial defects in the chromatin association of the MCM comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 36 publications
(54 reference statements)
2
18
0
1
Order By: Relevance
“…Comparatively, both yeast and human IPI3 interacted with ORC2 and MCM4 [9,28]. The collective evidence is consistent with human IPI3, being a licensing factor in pre-RC formation in both yeast and human cells.…”
Section: Interactions Of Yeast and Human Noc3 And Ipi3 With Orc And Msupporting
confidence: 68%
See 2 more Smart Citations
“…Comparatively, both yeast and human IPI3 interacted with ORC2 and MCM4 [9,28]. The collective evidence is consistent with human IPI3, being a licensing factor in pre-RC formation in both yeast and human cells.…”
Section: Interactions Of Yeast and Human Noc3 And Ipi3 With Orc And Msupporting
confidence: 68%
“…We have also previously reported that yIpi3p interacts with yOrc2p, yCdc6p, yCdt1p and yMcm4 [9] (Supplementary Figure S3 and Supplementary Table S1). We also reported that hIPI3 (WDR18) interacts with hORC1, hORC2, hORC3, hORC4, hORC5, hMCM2, hMCM3, hMCM4 and hMCM7 [28].…”
Section: Interactions Of Yeast and Human Noc3 And Ipi3 With Orc And Mmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition to the inter-subunit interactions that we and others previously reported (Matsuda et al, 2007;Chen et al, 2008;Huo et al, 2012;Wu et al, 2019), we found that Orc1p, Orc2p, Orc5p, and Orc6p have self-interactions, i.e., molecules of the same subunit interact with each other ( Figure 1A). Of note, yeast two-hybrid analysis based on the relative yeast growth rates on different selection stringencies, as we used in this study, favors the detection of direct physical interactions, most of which can be confirmed by other methods (Yu et al, 2004;Huo et al, 2012;Huang et al, 2016;Cheung et al, 2019;Wu et al, 2019; this study).…”
Section: Resultssupporting
confidence: 52%
“…In budding yeast, the six subunits of ORC and Noc3p bind to replication origins throughout the cell cycle, where they function as the origin recognition scaffold [3][4][5]. Pre-RC assembly begins at the M-to-G 1 transition with the loading of Cdc6p by Orc1-6p, Noc3p and Ipi3 [3][4][5][6], followed by the association of the Cdt1p-MCM2-7p heptamer [7][8][9][10][11][12][13][14][15][16]. After pre-RC assembly, replication origins are "licensed" and ready for firing (origin activation) [17][18][19].…”
Section: Introductionmentioning
confidence: 99%